Optimal thinking: how to be your best self - "Glickman, Rosalene" (Bhopal, 2010)
A revolutionary and mental tool that shows you how simple it is to sweep past the ordinary and even the extraordinary into the world of the highest and the best. Helps maximize talents, resources and time, to achieve optimum personal and professional satisfaction.
Keywords: Self improvement